2014 International Conference on Communication and Network Technologies 2014
DOI: 10.1109/cnt.2014.7062762
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of MAC using area efficient and reduced delay vedic multiplier targeted at FPGA architectures

Abstract: The Multiply-Accumulator (MAC) unit always lies in the critical path that determines the speed of the overall hardware systems. Therefore, a high-speed MAC that is capable of supporting multiple precisions and parallel operations is highly desirable. This paper describes the implementation of a MAC unit using area efficient Vedic multiplier which enhanced in terms of area and path delay. Speed of the multiplier is very important to any Digital Signal Processors (DSPs). To construct a NxN bit Vedic Multiplier, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Here, input a=6 (00000110) and input b=-7 (11111001) and obtained 16 bit result for same is -42 (1111111111010110) which is displayed on LCD as shown in Figure 13. In Table I, the combinational path delay, for signed Vedic multiplier implemented in [6] and proposed signed Vedic multiplier using carry select adder is shown and compared, it can be clearly observed that the combinational path delay for signed Vedic multiplier using carry select adder is less as compared with existing signed Vedic multiplier, along with this the result is also compared with conventional booth multiplier as seen in table I. Hence proving the effectiveness of proposed work.…”
Section: Fpga Implementationmentioning
confidence: 53%
See 2 more Smart Citations
“…Here, input a=6 (00000110) and input b=-7 (11111001) and obtained 16 bit result for same is -42 (1111111111010110) which is displayed on LCD as shown in Figure 13. In Table I, the combinational path delay, for signed Vedic multiplier implemented in [6] and proposed signed Vedic multiplier using carry select adder is shown and compared, it can be clearly observed that the combinational path delay for signed Vedic multiplier using carry select adder is less as compared with existing signed Vedic multiplier, along with this the result is also compared with conventional booth multiplier as seen in table I. Hence proving the effectiveness of proposed work.…”
Section: Fpga Implementationmentioning
confidence: 53%
“…The main limitations in the method proposed in [6] are, i) to calculate the final result of multiplication, the authors have used 3 adders, in which adder 1 is ripple carry adder, and other 2 adders are combination of half adder and full adder, hence the delay involved is more for calculation of final product. ii) Other than this, q0 of Figure 2 is passing to the adder 2 in existing method, which is also affecting delay of multiplier.…”
Section: Proposed Architecture: Handling Of Partial Product Usingmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional and proposed MAC unit is coded on verilog-HDL and XILINX ISE simulator. [5] The simulation on Spartan-3e family using XILINX ISE tool and coding on verilog. The result of delay is proposed multiplier is 41.562 ns and binary multiplier is 94.087.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This two 4-bit input multiplier first 2bit input multiplication by vertical and crosswise we start with LSB to MSB input multiplication and then addition of multiplication and to generated carry in previous one addition we added with next addition. [5] D.Design of 16x16 Bit Multiplier : This fig.6 to representation of block diagram of 16x16bit vedic multiplier using adder. Here two input given to 16-bit and we get the 32bit output data.…”
Section: Design Of 4x4 Bit Multipliermentioning
confidence: 99%